PERBEDAAN KEMAMPUAN MATEMATIKA SISWA KELAS I SD ANTARA YANG MENGIKUTI DAN YANG TIDAK MENGIKUTIPENDIDIKAN ANAK USIA DINI (PAUD) DI SDN 006 SALO KABUPATEN KAMPAR - Azura Azura; Wilson Wilson; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study aims to determine whether there are significant differences between the ability of first grade elementary mathematics students who follow and who do not follow the early childhood education at the SDN 006 Salo Kampar district. This type of research is comparative. Remembering the wide scope of the problem, the authors need to provide boundary problem to be studied namely the difference Mathematical ability elementary students in grade I follow and who do not follow the Early Childhood Education (ECE) at the SDN 006 Salo Kampar district. Data collection tool used in the form of documentation capabilities graders Math I. The population in this study were 006 students of Class I SDN Salo Kampar district, the overall number is as many as 26 students To determine the sample of this study, this study uses total sampling technique, which takes a sample of the total population that is 26 students. The variables in this study consists is, X1: Math ability level of students who take early childhood and X2: Math ability level of students who do not follow ECE. Based on the research results, the conclusion of this study is that there is a comparison. It can be seen from t is greater than the table ta (62.39> 2.064). Thus Ho is rejected and Ha accepted. In conclusion there are significant differences between the mathematical abilities of children who attend early childhood education and early childhood that do not followKeywords: Mathematical Ability, Following and Not Following ECE